Handbook of canine and feline emergency protocols - McMichael, Maureen (Hoboken : Wiley, 2014)
Handbook of Canine and Feline Emergency Protocols, Second Edition offers practical step-by-step guidance to managing emergency cases in small animal practice. Presenting more than 165 complete protocols for triaging, stabilizing, and managing emergent patients, the book is designed for fast access in an emergency situation, with a spiral binding and tabs to make it easy to flip to the relevant section. An ideal resource for veterinary practitioners seeking a quick reference for dog and cat emergencies, this Second Edition provides enhanced imaging information to increase the book's.
HypoadrenocorticismHistory; Clinical Signs; Diagnostics; Treatment; Prognosis; Feline Hyperthyroidism; History; Clinical Signs; Diagnostics; Treatment; Prognosis; Canine Hypothyroidism; History; Clinical Signs; Diagnostics; Treatment for Myxedema Coma; Prognosis; Hypocalcemia; History; Clinical Signs; Diagnostics; Treatment; Prognosis; Hypercalcemia; History; Clinical Signs; Diagnostics; Treatment; Prognosis; Further Reading; Chapter 5 Gastrointestinal Emergencies; Constipation/Obstipation; History; Clinical Signs; Diagnostics; Treatment; Prognosis; Esophageal Obstruction; History.
Clinical Signs.
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: Veterinary emergencies; Dogs -- Wounds and injuries -- Treatment; Dogs -- Diseases -- Treatment; Cats -- Wounds and injuries -- Treatment; Cats -- Diseases -- Treatment; Dogs -- Diseases -- Diagnosis; Heart diseases -- Veterinary; Veterinary electrocardiography; TECHNOLOGY & ENGINEERING -- Agriculture -- Animal Husbandry; Cats -- Diseases -- Treatment; Cats -- Wounds and injuries -- Treatment; Dogs -- Diseases -- Treatment; Dogs -- Wounds and injuries -- Treatment; Veterinary emergencies; Electronic books